The Influence of Presentation Format on Responses of Male Sex Offenders to Digital Paintings that illustrate the Consequences Sexual Crimes - Benta G. Adhiambo Oguda; George Vikiru; Christine Wasanga (Journal of Sociological Research, 2024)
Although art viewing experiences occur in varied contexts, responses of audience may be profoundly affected by the presentation format. In this paper, focus is drawn upon participation in a digital paintings exhibition and visual representation in assessing the responses of male sex offenders to digital paintings that illustrate the consequences of sexual crimes. The relationship between arts and technology is an emerging area of interest in modern research. In addition to the traditional gallery displays, digital technologies have provided new ways of audience participation in arts, enabling more involvement in the way art is consumed. The authors sought to determine the effect of viewing screen projected images in Rapid Serial Visual Presentation and in a gallery display. The study applied brief repeated exposures as described in Mere Exposure research. The study utilized temporary exhibition displays and projection by Rapid Serial Visual Presentation (RSVP) where the respondents were passive participants, simply viewing the artwork. The participants were drawn from male sexual offenders aged 18-45 years at Nairobi West Prison, a male offenders’ facility in Nairobi City County. Stratified random sampling was used to select 61 male offenders convicted for defilement and rape. Respondents were randomly assigned to two experimental conditions involving viewing in projection by RSVP and gallery display. A five-point Likert scale was used to measure the participants’ responses to digital paintings illustrating consequences of sexual crimes. A Multivariate Analysis was used to assess ratings of the digital paintings against the various components of art. Findings show that painting style, colour schemes, themes and exposure frequency significantly influenced the participants’ responses to the digital paintings. The study recommends use of comparative analysis to determine how exposure to digital paintings impacts differently on other types of audiences.